Hybrid High Solar Share Gas Turbine Systems with Innovative Gas Turbine Cycles. (May 2015) - Puppe, M.; Giuliano, S.; Krüger, M.; Lammel, O.; Buck, R.; Boje, S.; Saidi, K.; Gampe, U.; Felsmann, C.; Freimark, M.; Langnickel, U.
Abstract: In this paper results from an ongoing research project(HYGATE) are presented, which is performed to reduce the levelized cost of electricity (LCOE) and to increase the CO2 reduction potential of the solar-hybrid gas turbine plant concept (SHGT). Key improvements are the integration of thermal energy storage and the reduction of the operating temperature of the gas turbine to 950 °C. As a result the solar receiver can provide the necessary temperature for solar-only operation of the plant at design point - without using the auxiliary burner.Annual performance calculations and an economic analysis of four different plant concepts were performed. Those concepts were analyzed using innovative power block processes. In general, such systems offer reliable and dispatchable power with low specific CO2 emissions.A substantial decrease of CO2 emissions has been achieved all along the four variants compared to results of a previous project[1] . Compared to the defined reference molten salt solar tower the solar-hybrid gas turbine plants as of now yield higher plant efficiencies, but have a slightly lower potential for CO2 reduction. Among the SHGT plants the variants including a bottoming Organic Rankine Cycle (SHORCC and SHORCC-R) achieve the highest efficiencies but have significantly higher LCOE, caused by the high costs of the ORC components which are not yet commercially available in the requireddimensions. The solar-hybrid combined cycle plant (SHCC)and solar-hybrid gas turbine plant with quasi isothermal compression and recuperation (SHGT-ICR) perform best among the SHGT plants in terms of LCOE, and can be considered an interesting alternative to molten salt tower plants. Taking into account other factors, such as plant complexity and water consumption, an isothermal solar gas turbine plant shows the most potential advantages. However, theSHCC has the highest technological maturity and is a likely candidate for a future demonstration plant.